Extreme distal migration of a maxillary canine. - Shanmuhasuntharam, P.; Thong, Y.L. (Nature Publishing Group, 1990)
A case of extreme distal migration of the left maxillary canine is reported. The canine had erupted buccal to the contact area between the left second premolar and first molar. Past reports of similar ectopia are reviewed.